(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the conditions of modification of the widely used ion-exchange resin AN-31 with phosphoric acid. For this work, the industrially used anion containing an amino group was modified with phosphoric acid to obtain a polyampholyte with a new property of internal interaction of a close order, and its infrared spectrum was analyzed. The results of the IR spectrum analysis showed the presence of a N-H bond in the region of 3200-3500 cm-1. In the new ion-exchange material obtained by chemical modification of the industrial anionite AN-31, broadening of the peaks of N-H bonds in the region of 3200-3500 cm-1 was found, in addition, in the region of 1450-1500 cm-1 the formation of a newly formed N-P bond was recorded, and in the region of 1100-1250 cm-1 - the formation of P-O bonds.